The effects of supportive-expressive dynamic psychotherapy on the outcomes of bipolar disorder in men - Alireza Bornamanesh; Amirhoshang Mehryar; Hojatollah Javidi; Noshad Ghasemi (Shahrekord University of Medical Sciences, 2021)
Background and aims: Bipolar disorder (BD) is a chronic disorder with high recurrence rate and significant disability. BD is refractory to treatments and afflicted patients experience disease recurrence despite medication therapy. Therefore, appropriate psychosocial interventions are needed to improve the effectiveness of medication therapy and facilitate BD management. The aim of this study was to evaluate the effects of supportive-expressive dynamic psychotherapy (SEDP) on the outcomes of BD in men. Methods: This double-blind randomized clinical study was conducted in 2017-2018 using a two-group pretest-posttest design. Participants were thirty hospitalized men with BD conveniently selected from Khorshid hospital, Isfahan, Iran, and randomly assigned to an intervention (n = 15) and a control (n = 15) group. Participants in the control group received conventional medication therapy, while participants in the intervention group received conventional medication therapy as well as SEDP in twelve 60-minute one-to-one sessions. Participants in both groups completed the Bipolar Depression Rating Scale before, immediately after, three months after, and six months after the intervention. The SPSS program for Windows (v. 23.0) was employed to analyze the data via the analysis of covariance and the repeated measures analysis of variance. Results: Although the mean score of bipolar depression significantly decreased at the first posttest, the between-group difference was not significant (P > 0.05). However, the mean score of bipolar depression in the intervention group was significantly less than the control group at the second and the third posttests (P < 0.05). Conclusion: SEDP is effective in significantly reducing mood symptoms among men with BD.